2016
DOI: 10.1007/s00284-016-1121-x
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS Versus VITEK®2: Comparison of Systems for the Identification of Microorganisms Responsible for Bacteremia

Abstract: We evaluated the reliability and accuracy of the combined use of MALDI-TOF MS and classical ID VITEK2 to identify monomicrobial infection in blood culture bottles. In total, 70 consecutive positive blood cultures were included in this study. Positive blood culture bottles were subjected to Gram staining and subcultured on solid media. Isolates grown from such culture media were used for classical ID using VITEK2 system. In parallel, an aliquot was subjected to a lysing-centrifugation method and used for the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…However, an important difference observed is the automated microbiological identification method used by Huang et al 12 , Perez et al 5 and Delport et al 13 : matrix assisted laser desorption ionization-time of flight (MALDI-TOF). This methodology is technically superior to the VITEK® 2 compact 17,18 . MALDI-TOF identifies microorganisms in minutes, while the automated phenotypic method needs hours for identification.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important difference observed is the automated microbiological identification method used by Huang et al 12 , Perez et al 5 and Delport et al 13 : matrix assisted laser desorption ionization-time of flight (MALDI-TOF). This methodology is technically superior to the VITEK® 2 compact 17,18 . MALDI-TOF identifies microorganisms in minutes, while the automated phenotypic method needs hours for identification.…”
Section: Discussionmentioning
confidence: 99%
“…VITEK MS (bioMérieux) and Biotyper (Bruker Daltonics) are examples of commercially available MALDI-TOF systems [7,8]. A recent report revealed that the MALDI-TOF assay had high correspondence with a biochemical culture and test (44), and MALDI-TOF and 16S rDNA analysis also had high correspondence, proving that MALDI-TOF is a rapid and accurate method [44,45]. Skin diphtheroids had been regarded as contaminants until MALDI-TOF enabled species identification, and reports of them acting as pathogens has increased [46].…”
Section: Application Of Maldi-tofmentioning
confidence: 99%
“…are allocated as A. xylosoxidans / A. denitrificans on this platform (18), thus providing limited capacity for accurate species-level identification. Further, VITEK ® MS and other mass spectrometry-based platforms require a purified isolate to obtain an accurate speciation result, which limits the utility of this platform as it cannot be used directly on polymicrobial clinical specimens such as sputum, resulting in longer turn-around times, potentially incorrect antimicrobial treatment, and higher costs (19, 20). In addition, mass spectrometry-based equipment has a large upfront cost and footprint, rendering this method out-of-reach for smaller, less-resourced laboratories.…”
Section: Introductionmentioning
confidence: 99%